The Dynamics of Participatory Democracy in Indonesia: Between Ideality and Socio-Political Reality - Masrin; Suriya Noor (International Journal of Social Sciences and Humanities, 2025)
Participatory democracy is one of the democratic models that emphasizes the active involvement of citizens in the public decision-making process. This concept was born as a criticism of procedural democracy which tends to be elitist and only emphasizes the formal aspects of elections. In Indonesia, the practice of participatory democracy began to develop in line with the 1998 political reform that opened up space for freedom of opinion and expanded public access to control the running of government. However, the ideal of participatory democracy is not always in line with the socio-political reality on the ground. Structural barriers, such as rigid bureaucracy, a culture of patronage politics, dominance of political elites, and limited public political literacy, often reduce the effectiveness of participation. This article aims to analyze the dynamics between the ideals of participatory democracy and the reality of its practice in Indonesia. The research method uses a qualitative approach by studying the literature, analyzing documents, previous research results, and regulations related to political participation. The results of the study show that despite significant progress in public engagement, participatory democratic practices are still characterized by unequal access, transactional practices, and weak institutionalization of participation spaces. The discussion emphasized the importance of strengthening civil society capacity, sustainable political education, and policies that support substantive participation. This article concludes that participatory democracy in Indonesia is at the intersection of normative expectations and complex practical realities, thus requiring adaptive strategies that integrate democratic ideals with local socio-political conditions.